2009
DOI: 10.1007/s11095-009-9990-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically-Based PK/PD Modelling of Therapeutic Macromolecules

Abstract: Therapeutic proteins are a diverse class of drugs consisting of naturally occurring or modified proteins, and due to their size and physico-chemical properties, they can pose challenges for the pharmacokinetic and pharmacodynamic studies. Physiologically-based pharmacokinetics (PBPK) modelling has been effective for early in silico prediction of pharmacokinetic properties of new drugs. The aim of the present workshop was to discuss the feasibility of PBPK modelling of macromolecules. The classical PBPK approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…In a PBPK model, a flow balance is kept by ensuring that the sum of input flows (ie, blood+lymphatic flow) is equal to the sum of output flows for each compartment. A schematic chart of a PBPK model can be found in many publica tions [12,30,31] . Overall, model-based drug development takes advantage of a series of quantitative approaches, such as mechanism-based PK, PBPK, PK-PD, exposure-response, and PK-PD-clinical response models.…”
Section: Mechanism-and Physiologically-based Models For Mabsmentioning
confidence: 99%
“…In a PBPK model, a flow balance is kept by ensuring that the sum of input flows (ie, blood+lymphatic flow) is equal to the sum of output flows for each compartment. A schematic chart of a PBPK model can be found in many publica tions [12,30,31] . Overall, model-based drug development takes advantage of a series of quantitative approaches, such as mechanism-based PK, PBPK, PK-PD, exposure-response, and PK-PD-clinical response models.…”
Section: Mechanism-and Physiologically-based Models For Mabsmentioning
confidence: 99%
“…However, physiologically based PK (PBPK) models have become a powerful alternative to classic compartmental models because they provide a mechanistic approach that 1) relates drug disposition to various physiological, anatomical, and physicochemical factors (Thygesen et al, 2009) and 2) offers a strong basis for interspecies, tissue, route, and drug extrapolations (Nestorov, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of PBPK modeling for macromolecules can be found in Thygesen et al (16). Once the target is selected and validated, the emphasis may then be to optimize the mAb's properties, albeit some of this effort may have already been underway or happening in parallel.…”
Section: Physiologically Based Pharmacokineticsmentioning
confidence: 99%
“…During the SB/SP phases ( Fig. 1), beyond the basic assessment of PK, time may be afforded to build a PBPK model to gain a better understanding of the mAb's tissue distribution characteristics (16)(17)(18). Such a model could assist in determining whether the mAb is adequately exposed to the intended tissue or site of action.…”
Section: Physiologically Based Pharmacokineticsmentioning
confidence: 99%